Restorative Justice in the New Criminal Code in Indonesia: A Prophetic Legal Study: Keadilan Restoratif pada KUHP Baru di Indonesia: Suatu Studi Hukum Profetik - Flora, Henny Saida (Rechtsidee, 2022)
The existence of Law No. 1 of 2023 concerning the Criminal Code (UU KUHP) as the new Criminal Code (KUHP) in Indonesia seeks to apply the legal ideals of Restorative justice is one of the concepts substantively constructed in the newly ratified Criminal Code. This study aims to analyze the existence and implications of restorative justice after ratifying the Draft Criminal Code (RKHUP) as a law. This research is normative legal research with statutory and conceptual approaches. The results of the study confirm that the existence of the concept of restorative justice from a prophetic law perspective fulfills the three fundamental values of prophetic law, namely: divinity, humanity, and justice. So, that the application of restorative justice in a prophetic law perspective strengthens the substance of the legal state of Indonesia as a nation-state based on the Godhead. Almighty. The implications of restorative justice after the ratification of the RKUHP became the Criminal Code Law in the perspective of prophetic law; that is, the substance of restorative justice has been facilitated in the Criminal Code Law and is spread across various articles. One of the affirmations in the Criminal Code Law is that punishment must not demean human dignity, which means protecting human dignity is God's commandment and a person who ignores the dignity of fellow human beings is a person who transgresses limits. Thus, who can conclude that the substance of restorative justice facilitated in the Criminal Code Act is relevant to prophetic law.